2008
DOI: 10.1103/physrevd.78.114018
|View full text |Cite
|
Sign up to set email alerts
|

ρρinteraction in the hidden gauge formalism and thef0(1370)andf

Abstract: The ρρ interaction in the hidden gauge formalism and the f 0 (1370) and f 2 (1270) resonances. AbstractWe have studied the interaction of vectors mesons within the hidden gauge formalism and applied it to the particular case of the ρρ interaction. We find a strong attraction in the isospin, spin channels I,S=0,0 and 0,2, which is enough to bind the ρρ system. We also find that the attraction in the I,S=0,2 channel is much stronger than in the 0,0 case. The states develop a width when the ρ mass distribution i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
430
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 228 publications
(457 citation statements)
references
References 45 publications
24
430
2
1
Order By: Relevance
“…After that, the radiative decay of these states into γγ was studied in [35], obtaining results in good agreement with the PDG [36]. The work of [34] was later extended to SU(3) [37], where several states were found that could also be identified with some of the PDG. Recently, the ρD * , ωD * interaction was studied within the same formalism [38], generalizing to SU(4) the basic hidden gauge Lagrangians, but breaking the SU(4) symmetry in the vector exchange diagrams.…”
Section: −65mentioning
confidence: 55%
See 2 more Smart Citations
“…After that, the radiative decay of these states into γγ was studied in [35], obtaining results in good agreement with the PDG [36]. The work of [34] was later extended to SU(3) [37], where several states were found that could also be identified with some of the PDG. Recently, the ρD * , ωD * interaction was studied within the same formalism [38], generalizing to SU(4) the basic hidden gauge Lagrangians, but breaking the SU(4) symmetry in the vector exchange diagrams.…”
Section: −65mentioning
confidence: 55%
“…In the present work we shall present results for the case of all the channels which couple to D * D * or D * sD * s . The formalism is the same used in [34] and [38]. Some approximations were made there which make the formalism handy and reliable, by neglecting the three-momentum of the vector mesons with respect to their masses.…”
Section: Lagrangianmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al also took into account some decay mechanisms by considering the decay of the states to a light baryon plus either a light meson or a charmonium through heavy charmed meson exchanges, as done in Refs. [291,292]. Table 12: Mass (M), total width (Γ), and the partial decay width (Γ i ) for the states from PB → PB, with units in MeV, taken from Refs.…”
Section: Dynamically Generated Resonancementioning
confidence: 99%
“…The self-energy Π ρ,(b) K * has to be determined self-consistently since it is obtained from the in-medium amplitude T ρ K * N which contains theK * N loop function G ρK * N , and this last quantity itself is a function of the complete self-energy Π ρK * = Π a2), taking all the cuts into account properly, and adding the resultinḡ K * N →K * N terms to the V B → V ′ B ′ potential coming from vectormeson exchange, in a similar way as done for the study of the vector-vector interaction in Refs. [21,22]. Preliminar results of this procedure in free space indicate that the generated resonances barely change their position for spin 3/2 and only by a moderate amount in some cases for spin 1/2.…”
Section: Contributions To Thek * Self-energymentioning
confidence: 99%